2017
DOI: 10.1039/c6tc03812c
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer based extended-gate field-effect transistor chemosensors for phenylalanine enantioselective sensing

Abstract: aeChemosensing systems were devised for the enantioselective determination of D-and L-phenylalanine (D-and L-Phe). As recognition units of these systems, molecularly imprinted polymers (MIPs) were designed, guided by DFT calculations, and then synthesized. For the preparation of these MIPs, carboxy derivatized bis(bithiophene) was used as the functional monomer. Both templated and templateextracted MIP films as well as non-imprinted polymer (NIP) films were characterized by IR spectroscopy to prove Phe temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Likewise, another work published by Iskierko and co-authors described two EG-FET based MIP sensors for a selective detection of specific phenylalanine enantiomers, d - and l -phenylalanine (Phe). Thus, the authors present successful sensors able to recognize levels of d - and l -Phe under 13 to 100 µmol/L with a LOD of 13 µmol/L and a good discrimination of interfering substances, such as d -proline, d -alanine, and d -tyrosine [174]. …”
Section: Electrochemical Transductionmentioning
confidence: 99%
“…Likewise, another work published by Iskierko and co-authors described two EG-FET based MIP sensors for a selective detection of specific phenylalanine enantiomers, d - and l -phenylalanine (Phe). Thus, the authors present successful sensors able to recognize levels of d - and l -Phe under 13 to 100 µmol/L with a LOD of 13 µmol/L and a good discrimination of interfering substances, such as d -proline, d -alanine, and d -tyrosine [174]. …”
Section: Electrochemical Transductionmentioning
confidence: 99%
“…MIPs have multiple advantages including easy and cost-friendly preparation, high stability, high affinity and selectivity toward template molecule. In addition, MIPs can be employed in different areas, such as sensors [13,14], enzyme mimics [15,16], solid phase extraction [17], antibody mimics [18], enantioselective [19], biomarker [20,21] protein recognition and purification [22,23], food safety [24], sensing of microorganisms [25], drug analysis [26,27,28], drug delivery system [29], hormone detoxification [30], food and environmental analysis [31]. Sensors are self-contained integrated devices which are able to convert chemical signal depending on analyte concentration into a measurable analytical signal [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Mulla et al [ 12 ] measured the weak chiral interactions associated with neutral enantiomers and found that they differentially bind to odorant binding proteins (OBPs) by bio-FET. Iskierko et al [ 13 ] used an extended-gate metal-oxide semiconductor field-effect-transistor (EG-MOSFET) with a detection limit of 13 μM for the enantioselective determination of phenylalanine isomers. The above research tells us that FET has great potential for chiral recognition.…”
Section: Introductionmentioning
confidence: 99%